2022
DOI: 10.1007/s00170-022-10126-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and prediction of central cracking in cross wedge rolling

Abstract: Central cracking refers to the formation of internal cavities in cross wedge rolling (CWR) products. It occurs in various materials such as aluminium/titanium alloys, steels and plasticine at room or elevated temperatures, driven by different central cracking mechanisms. However, these mechanisms are still elusive, and a unified central cracking predictive model is absent due to the complex stress states within the workpiece, including triaxial stress states, cyclic loading and severe shear effects. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…It was found that under the temperature of CWR, due to the differen thermal expansion coefficients and elasticity of steel matrix and inclusions, micro voids o cracks are generated around the inclusions, which is the main reason for the central crac ing of rolled parts. Zhou et al [27,28] used model material to simulate the material flo and internal fracture behavior in the CWR workpiece, determined that the maximu shear stress is the dominant factor of the central damage, and established a damage mod considering the joint influence of the maximum shear stress and the first principal stres Shi et al [29] found that the volume of central defects during CWR TC4 Aeroengine blade is closely related to the initial rolling temperature of the billet. When the rolling temper ture of TC4 billet is higher than 850 °C, the target rolled parts without central defects ca be obtained.…”
Section: Research Methods Of Central Defects In Cwr the Railway Axlementioning
confidence: 99%
“…It was found that under the temperature of CWR, due to the differen thermal expansion coefficients and elasticity of steel matrix and inclusions, micro voids o cracks are generated around the inclusions, which is the main reason for the central crac ing of rolled parts. Zhou et al [27,28] used model material to simulate the material flo and internal fracture behavior in the CWR workpiece, determined that the maximu shear stress is the dominant factor of the central damage, and established a damage mod considering the joint influence of the maximum shear stress and the first principal stres Shi et al [29] found that the volume of central defects during CWR TC4 Aeroengine blade is closely related to the initial rolling temperature of the billet. When the rolling temper ture of TC4 billet is higher than 850 °C, the target rolled parts without central defects ca be obtained.…”
Section: Research Methods Of Central Defects In Cwr the Railway Axlementioning
confidence: 99%
“…Zhou et al [ 44 ] performed the numerical analysis of CWR using Deform 3D, finding that the maximum shear stress τ max caused the formation of internal voids that would then develop into cracks due to the impact of the maximum principal stress σ 1 . Zhou et al [ 45 , 46 ] proposed a new stress-based criterion that took into account the effect of both τ max and σ 1 . A total of 12 cases of CWR taken from the literature were modeled numerically by this criterion, showing that the criterion was an effective tool for predicting material fracture in CWR.…”
Section: Materials Fracture In Cwrmentioning
confidence: 99%